Nature of truancy from the perspectives of secondary students in New Zealand. Issue 1 (2nd January 2023) - Baskerville, Delia; Loveridge, Judith
ABSTRACT: Truancy is a long-standing and serious educational issue. The debates surrounding truancy are complex as the concept of truancy means different things to different researchers. Data from a grounded theory, qualitative doctoral study is used to investigate how a sample of thirteen young people explained the nature of truancy, which they referred to as wagging. Findings in this study show that, according to young people who wag, there are four dimensions when they define the nature of wagging: wagging as a response to perceived disrespect in class; wagging to be with friends; wagging as a time to be alone and wagging as habit. On the basis of student perspectives, we argue the importance of early interventions to prevent the development of habitual wagging. A focus on inclusive teaching and social practices to ensure support and promotion of student well-being is required.